Monitoring stress and recovery states: Structural and external stages of the short version of the RESTQ sport in elite swimmers before championships - Nicolas, M.; Vacher, P.; Martinent, G.; Mourot, L. (Journal of Sport and Health Science, 2019)
Background: Psychological stress and recovery monitoring is a key issue for increasing athletes' health, well-being, and performance. This multi-study report examined changes and the dose-response relationships between recovery-stress psychological states, training load (TL), heart rate (HR), heart rate recovery (HRR), and heart rate variability (HRV) while providing evidence for the factorial validity of a short French version of the Recovery-Stress Questionnaire for Athletes (RESTQ-36-R-Sport). Methods: Four hundred and seventy-three university athletes (Study 1), 72 full expert swimmers (Study 2), and 11 national to international swimmers (Study 3) participated in the study. Data were analyzed through confirmatory factor analyses (Study 1), repeated ANOVAs and correlational analyses (Study 2), t tests and correlational analyses (Study 3). Results: Multiple-group confirmatory factor analyses showed that the RESTQ-36-R-Sport scores were partially invariant across gender, type of sport, and practice level (Study 1). A dose-response relationship was performed between TL and RESTQ-36-R-Sport scores during an ecological training program (Study 2). Finally, relationships were found between physiological (HRR) and psychological (RESTQ-36-R-Sport) states during an ecological tapering period leading to a national championship (Study 3). Conclusion: As a whole, these findings provided evidence for the usefulness of the short version of the RESTQ-36-R-Sport for regular monitoring to prevent potential maladaptation due to intensive competitive sport practice.